Sensory Input-Dependent Changes in Glutamatergic Neurotransmission- Related Genes and Proteins in the Adult Rat Trigeminal Ganglion - Fernández-Montoya, Julia; Buendia, Izaskun; Martin, Yasmina B.; Egea, Javier; Negredo, Pilar; Avendaño, Carlos (Frontiers in Molecular Neuroscience, 2016)
Experience-dependent plasticity induces lasting changes in the structure of synapses, dendrites and axons at both molecular and anatomical levels. Whilst relatively well studied in the cortex, little is known about the molecular changes underlying experience-dependent plasticity at peripheral levels of the sensory pathways. Given the importance of glutamatergic neurotransmission in the somatosensory system and its involvement in plasticity, in the present study, we investigated gene and protein expression of glutamate receptor subunits and associated molecules in the trigeminal ganglion (TG) of young adult rats. Microarray analysis of naïve rat TG revealed significant differences in the expression of genes, coding for various glutamate receptor subunits and proteins involved in clustering and stabilization of AMPA receptors, between left and right ganglion. Long-term exposure to sensory-enriched environment increased this left-right asymmetry in gene expression. Conversely, unilateral whisker trimming on the right side almost eliminated the mentioned asymmetries. The above manipulations also induced side-specific changes in the protein levels of glutamate receptor subunits. Our results show that sustained changes in sensory input induce modifications in glutamatergic transmission-related gene expression in the TG, thus supporting a role for this early sensory-processing node in experience-dependent plasticity.